Degree of Satisfaction With Telemedicine Service Among Health Practitioners and Patients in Saudi Arabia - Salem S. Albagmi; Mohammed S. Shawaheen; Humood Albugami; Albandari Alshehri; Raghad Alblwie; Wadha Alsiari (International Journal of Telemedicine and Applications)
The satisfaction level of patients and physicians with telemedicine services should be comparable to on-site visits if this technology is to be widely adopted. The degree of satisfaction can be used to assess the performance of any healthcare service. Therefore, in this cross-sectional study, we used a five-point Likert scale to evaluate the level of satisfaction with telemedicine by administering survey questionnaires to both patients and physicians online residing across Saudi Arabia. The questionnaires were divided into three parts: consent and summary, demographics, and the survey questions to determine satisfaction level with telemedicine. All statistical analysis was performed using SPSS Version 27. The results showed high satisfaction levels with telemedicine services by both patients and physicians where the age and gender of participants were influential in determining this outcome. Residential areas affected satisfaction levels with telemedicine in physicians but not in patients. Previous experiences with these services influenced the satisfaction of patients with those having previous experience reporting higher satisfaction. However, when the degree of satisfaction between patients and physicians was compared, the results were insignificant showing that the overall perception towards telemedicine usage is similar between healthcare providers and receivers. To conclude, our study showed that the experiences of patients and physicians with telemedicine services are satisfactory; however, certain areas regarding telemedicine usage warrant further improvement.